Strengthening disaster data systems in the Indian Ocean (UNDRR, 2026)
Seychelles hosted a regional peer learning workshop on building methodological foundations for national disaster tracking systems powered by DELTA-Resilience. Participants from Seychelles, Mauritius and Madagascar attended.